The Boer and the Jackal: Satire and resistance in Khoi orature - Wittenberg, Hermann (Multilingual Margins: A journal of multilingualism from the periphery, 2023)
Bushman narratives have been the subject of a large volume of scholarly and popular studies, particularly publications that have engaged with the Bleek and Lloyd archive. Khoi story-telling has attracted much less attention. This paper looks a number of lesser known Khoi narratives, collected by Thomas Baines and Leonhard Schultze. Despite commonalities in the respective oral traditions, Khoi folklore appears more open to discursive modes of satire, mockery and ridicule, features which are not readily found in Bushman story telling. A number of Khoi narratives that feature the trickster figure of the jackal are presented and analysed as discursive engagements with historical realities and political forces that impinged on indigenous societies. It is argued that Khoi orature was able to mock and subvert settler dominance by making imaginative use of animal proxies such as the jackal. This capacity for satire in Khoi oral culture allowed it to resist colonial violence on a discursive level, a strategy that was much less pronounced in Bushman narration.